The implications of China’s economic statecraft in the European Union : the case of chinese foreign direct investment in Portugal - Santos, Luís Pedro Moço da Costa (2021)
This thesis contributes to the analysis of Chinese economic statecraft in the European Union, by zooming on the Chinese Outward Foreign Direct Investment (COFDI) in Portugal. Understanding economic statecraft as the usage of economic instruments in pursuit of political objectives, this work investigates the political and strategic implications of COFDI in Portugal. While many regard COFDI as a lifeline, others fear it to be politically motivated and part of a Chinese masterplan to convert economic power into political influence. But what type of political influence can China aspire to acquire, and under what conditions? This thesis is pioneer in providing an exhaustive library of investment case studies about all COFDI cases in Portugal between 2011 and 2019. It also surfaces how the potential implications of COFDI are perceived by the key domestic stakeholders, such as senior government officials, business executives, representatives from local Chinese institutions and other opinion makers. Zooming in on the investment cases reveals insights regarding the motivations behind COFDI and its operationalization patterns. Chinese investors are willing to have non-controlling stakes in assets which provide other strategic returns, such as access to know-how or to the Portuguese speaking markets. Through the interviews with key stakeholders, it was possible to identify four clusters based on the interviewees perceptions of COFDI, and extract the overall picture - the prevailing approach to COFDI is that of confidence on the country’s ability to have the cake and eat it too. This means using COFDI as a proxy for domestic capital (which is scarce), balancing it against the dependence from western powers and pulling all parties to invest further in the country, with due awareness about tangible security implications.